2014
DOI: 10.1038/ncomms4461
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the charge carrier separation and working mechanism of CH3NH3PbI3−xClx perovskite solar cells

Abstract: Developments in organic-inorganic lead halide-based perovskite solar cells have been meteoric over the last 2 years, with small-area efficiencies surpassing 15%. We address the fundamental issue of how these cells work by applying a scanning electron microscopy-based technique to cell cross-sections. By mapping the variation in efficiency of charge separation and collection in the cross-sections, we show the presence of two prime high efficiency locations, one at/near the absorber/hole-blocking-layer, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
504
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(538 citation statements)
references
References 27 publications
31
504
1
2
Order By: Relevance
“…Therefore, the FTO layers are the n þ þ electrodes. Reports in literature have shown that some lead halide perovskite solar cells behave as p-i-n cells 3,[16][17][18] . Our lead halide perovskites thin films are highly resistive and have low carrier concentrations, typically below the sensitivity of our Hall measurement system (B10 14 cm À 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the FTO layers are the n þ þ electrodes. Reports in literature have shown that some lead halide perovskite solar cells behave as p-i-n cells 3,[16][17][18] . Our lead halide perovskites thin films are highly resistive and have low carrier concentrations, typically below the sensitivity of our Hall measurement system (B10 14 cm À 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, methods such as Kelvin probe force microscopy (KPFM) [148,149] and electron-beam-induced current (EBIC) measurements [150,151] allowed for the measurement of the potential and current distribution within a device, providing more direct evidence for a charge trapping and detrapping process. In these experiments, the charge-carrier-density distribution across the cross-section of the device was measured, allowing one to track the evolution of accumulated charges after illumination.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…It has been already reported that CH 3 NH 3 PbI 3 forms two active junctions: one with the n-type TiO 2 and the other with p-type spiro-OMeTAD. 20 The interface between TiO 2 and CH 3 NH 3 PbI 3 shows a huge lattice mismatch. 15 These mismatches produce high electrical capacitance at the interface.…”
Section: ¹2mentioning
confidence: 99%